Characterizing agronomic, morphological, nutritional, and phytochemical traits of local sorghum (Sorghum bicolor L.) in Indonesia - Banna, Maisya Zahra Al; Arifuddin, Widiastini (Universitas Lancang Kuning, 2024)
South Sulawesi has been designated by the Ministry of Agriculture, Indonesia, as a key sorghum-producing province. The known sorghum varieties from South Sulawesi include Batara Tojeng Eja, Batara Tojeng Bae, and local sorghum from Jeneponto. In Bulukumba Regency, South Sulawesi Province, Indonesia, local farmers traditionally cultivate local sorghum alongside maize. This study aims to gather information on the agronomic traits, morphological characteristics, nutritional composition, and phytochemical content of local sorghum from Tritiro village, Bulukumba Regency. Agronomic and morphological traits were analyzed through observations of growth and phenotypic features of the leaves, stems, roots, panicles, and seeds of sorghum. Nutritional composition was measured quantitatively, while phytochemical screening was conducted both qualitatively and quantitatively. The results show that local Tritiro sorghum has medium plant height, small stem diameter, medium panicle length, loose panicle shape, and brown seeds. Nutritional analysis revealed that local Tritiro sorghum contains 10.11% protein, 0.19% fat, 86.73% carbohydrates, 68.97% starch, and 9.43 mg g⁻¹ tannins. Local Tritiro sorghum has higher carbohydrate, protein, and fiber content compared to other sorghum varieties from South Sulawesi and exhibits higher tannin content. These findings highlight the potential of local Tritiro sorghum as a valuable nutritional resource and its suitability for cultivation in the region, contributing to food security and sustainable agricultural practices.